1995
DOI: 10.1109/94.484315
|View full text |Cite
|
Sign up to set email alerts
|

State of water in hydrocarbon liquids and its effect on conductivity [transformer oil]

Abstract: A B S T R A C TThe humidity or the dissolved water in insulating oils influences conduction and breakdown phenomena. The corrections between the amount of dissolved water and the electrical properties have been investigated. However, the effect of water has been based only on the total amount of water because in the past there was no way to observe the state of water in oil in an electrical field. With the availability of Fourier transform infrared (FTIR) to characterize water clusters, the effect of water in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Figure 3 illustrates this behavior for a variety of hydrocarbons as a function of water content. 3 Figure 4 from the same reference shows that conductivity of the w/o solution is not only a function of water content but a strong function of the type of hydrocarbon.…”
Section: Water Dissolved In Oilmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 3 illustrates this behavior for a variety of hydrocarbons as a function of water content. 3 Figure 4 from the same reference shows that conductivity of the w/o solution is not only a function of water content but a strong function of the type of hydrocarbon.…”
Section: Water Dissolved In Oilmentioning
confidence: 94%
“…This was attributed by the authors to the polarizability of the unsaturated and aromatic hydrocarbons compared to the saturated hydrocarbons. 3 Conductivity of the solution is a convenient means to estimate qualitatively the corrosiveness of a solution, since corrosion rates generally increase with increasing solution conductivity. Although the corrosion current is the sum of all reaction steps in the system, if one of those steps has a conductivity significantly less than the others, it will be rate controlling.…”
Section: Water Dissolved In Oilmentioning
confidence: 99%
“…At low concentrations, water is thought to reside at the solid-liquid interface due to its hydrophilic nature, while at higher concentrations, water may exist as dispersed droplets and at very high concentrations as an emulsion. Itahashi et al [50] indicated that water exists in two states in hydrocarbon liquids: for saturated hydrocarbons water exists as 'free water', but in unsaturated hydrocarbons and hydrocarbon-containing heteroatoms (such as oxygen, sulphur, and nitrogen) water combines with these molecules (probably through hydrogen bonding). For oxidation, the uncontaminated L1 level gives the lowest friction, while L2 and L3 give the highest friction and L4 produces lower friction levels.…”
Section: Effect Of Contaminants On Wearmentioning
confidence: 98%
“…The measurements show that the oil conductivity is essentially independent of the moisture content. These results agree with those of Itahashi, et al [2] but disagree with those of Higaki, et al [3], possibly because the system studied by Higaki, et al included pressboard which may have released impurities into the oil. The apparent increase in conductivity with moisture content at 70°C is probably due to oil oxidation, rather than moisture, since the oil was exposed to air.…”
Section: Cair Zlrsupporting
confidence: 86%